Spatial Analysis of Variations in Level of Living within the Ibadan Metropolitan Region. - Yirenkyi-Boateng, S (Obafemi Awolowo University, 2014)
In recent years, increasing attention has been devoted to the living conditions of people in formulating national development plans. Similarly, geographers interested in the regional dimension of development now take greater cognizance of issues related to level of living. This thesis is a contribution to this growing area of regional development. It investigates the spatial dimension of development as related to level of living at the city level. Ibadan has been selected for this purpose. 2403 households were selected for the study from 30 residential zones in Ibadan based on 23 variables. The techniques adopted in analysing the data are factor and regression analyses, cluster analysis and causal modeling analysis. The investigation revealed the following findings: (i) The factors or dimensions underlying the relation-ships between the 23 variables were found to reflect three broad social classes in Ibadan: the upper class, poor working class and middle class factors, which contributed 60.75%, 19.36% and 6.80% respectively to the total variance. (ii) The three social classes were observed to owe their existence largely to institutional and traditional factors with their particular spatial patterns in Ibadan. Whilst the institutionalized high class residential areas displayed multiple nuclei patterns in the city, the newly emerging slums associated with the poor working class factor displayed arc-like patterns on the outskirts of the city. The middle class factor generated multiple nuclei and sectoral spatial patterns. However at the aggregate level, it was observed through regression analysis, that there was a general increase level of living from the centre of Ibadan to the periphery. (iii) Causal links were also found to exist between the factors and their associated spatial patterns- a situation which tends to perpetuate existing conditions. (iv) Five major residential groups were obtained application of cluster analysis. These five groups represented the broad frame work within which the variations in level of living within the Ibadan metropolis could be discussed. From the findings, it has been proposed that the traditional and institutional factors would have to undergo major changes before considerable improvements in the general living conditions of the population of Ibadan could be achieved. It has also been suggested that social area analysis should specifically focus on the level of living dimension which is a crucial factor in the development process.